On floating exchange rates, currency depreciation and effective demand - Lopez, Julio; Perrotini, Ignocio Perrotini (PSL Quarterly Review, 2012)
This paper discusses the relative advantages of floating exchange rates vis-a-vis a pegged exchange rate regime, with special emphasis on the implications foreffective demand. More particularly, it explores whether a currency depreciationhas a beneficial effect on aggregate demand and hence on employment. The authors argue that this issue is central to the whole principle of effective demand, and that the idea of a currency depreciation being able to stabilize effective demand is to a large extent analogous to the claim that (downward) flexibility of nominal (and real) wages can ensure full employment. Accordingly, the relationship between downward wage flexibility and effective demand is analysed and the hypothesis that exchangerate flexibility can have stabilizing properties when exogenous shocks of various kinds are taken into account is critically assessed both theoretically and empirically. The paper concludes that while exchange rate flexibility can be a useful instruments, it may have some side effects that should be taken into account. JEL Codes: E24, F33